Effects of Sensory-Motor Training on Fine Motor Skills and Psychological Well-Being of Children with Hearing Impairment - Ghamar Mehri; Hasan Mohammadzadeh; Malek Ahmadi (University of Tehran, 2023)
Introduction: Hearing impairment is a type of children's sensory disorder that cause problems in the daily life of children and parents. This research aimed to determine the effect of sensory-motor training on fine motor skills and the psychological well-being of children with hearing impairment.Methods: This applied research was a quasi-experimental type with a pre-test and post-test design. The statistical population included children with a hearing impairment from the elementary exceptional student education center in Ardabil City. To participate in this research, the hearing threshold of each student was measured using an audiometer. By using the convenience sampling method, 20 samples were selected and assigned to two control (N=10) and experimental (N=10) groups. The measurement tools included Peabody Developmental Motor Scale (PDMS) for fine motor skills and the Strengths and Difficulties Questionnaire (SDQ) for psychological well-being assessment. No training was given to the groups before the intervention. The experimental group performed 45-minute sessions of sensory-motor integration training for eight weeks and six days a week, by imitating the coach's movements and trying to coordinate with the group at the same time. The control group participated in daily activities. The analysis of the covariance (ANCOVA) test was used for statistical analysis.Results: sensory-motor integration training had a significant effect on improving children's fine motor skills and well-being and cause improvement in the levels of both factors.Conclusion: Participating in sensory-motor training can be of great help in reducing motor and psychological problems of children with hearing impairment.